A Smart Solution for Fuel Smuggling Problem: The Reality and Challenges, Case Study of the Southern Region of Libya . - Samba, Mohammed Alsharif; Li, Yiqian; Shamus, (Journal of Earth Energy Engineering, 2022)
The phenomenon of smuggling is a crime that threatens countries in general. It is considered as a challenge for all countries to overcome this problem. The danger increases when the goods of smuggling are one of the most important natural resources in the country, which is the smuggling of oil or one of the oil derivatives, among which is fuel in a remarkable way. Where the smuggling groups smuggle the fuel across the land borders of south Libya. Given the presence of this crime, we are trying to shed light on it by asking many questions and knowing the position of the Libyan legislator regarding it. Were the solutions that decided useful or not? This paper was written as a result of the suffering suffered by the people in the south of Libya as a result of this crisis. However, the crise has described in general and provided the ideal solution that should be applied in all the countries. The solution was represented full system for the fuel distribution. The system is supported by monitoring sensors, indication sensors, and an artificial neural network system.